Stock returns and bond yields in Denmark, 1922-99 - Steen Nielsen; Ole Risager (Copenhagen Business School (CBS), Department of Economics, 2001)
This paper presents long time series of stock and bond returns for Denmark from 1922 to 1999. Average stock returns are low in an international context, but returns (and volatility) have increased sharply since 1983 which may be explained by major changes in economic policy and liberalizations of capital flows. On the other hand, Danish bond yields are high in general, and in particular from the late 1960s to the mid 1980s. Thus, there are several periods in which bonds have given higher returns than stocks. Over the entire sample, however, equity clearly outperforms bonds.
hdl:10398/7649
Keywords: G00; 330; Stock market; Bond Yields; Denmark